2022
DOI: 10.3390/ijerph19053026
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Entomological and Epidemiological Efficacy of Pyriproxyfen-Treated Ovitraps in the Reduction of Aedes Species: A Quasi-Experiment on Dengue Infection Using Saliva Samples

Abstract: Our study assessed the impact of using ovitraps with pyriproxyfen on mosquito populations and the feasibility of using human saliva samples to test for seroconversion to dengue virus (DENV). We used a quasi-experimental research design by forming the intervention (n = 220) and the control (n = 223) groups in neighboring Taguig City, Philippines, over 4 months. Socio-demographic data, entomological indices, and IgG antibodies against DENV were measured. Associations between the implementation of ovitraps dosed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the Philippines, previous research tackled the use of AD-PPF in a small urban community in Metro Manila using a small sample size in which results showed that dengue seroconversion rates decreased in the treated population but not significantly so. The authors hypothesized that the use of PPF-treated ovitraps may have impacted the mosquito population but not the seroconversion rates [25]. Our study, which examined the pattern of the spatial distribution of DENV infection in two research sites in Parañaque City, may rectify the limitations seen from the previous AD-PPF research.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the Philippines, previous research tackled the use of AD-PPF in a small urban community in Metro Manila using a small sample size in which results showed that dengue seroconversion rates decreased in the treated population but not significantly so. The authors hypothesized that the use of PPF-treated ovitraps may have impacted the mosquito population but not the seroconversion rates [25]. Our study, which examined the pattern of the spatial distribution of DENV infection in two research sites in Parañaque City, may rectify the limitations seen from the previous AD-PPF research.…”
Section: Discussionmentioning
confidence: 93%
“…Individuals recruited for seroconversion were those within 200 meters of the household of the index dengue case and within 10 meters of the autodissemination and ovitrap stations. At the time of recruitment, AD-PPF devices (Ovitraps filled with 250 mL of water with one sachet of Sumilarv™ 0.5 G Sumitomo Chemical as previously described elsewhere [25]. were placed in the chosen households in the intervention study site houses.…”
Section: Control and Intervention Ovitrap Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals recruited for seroconversion were those within 200 m of the household of the index dengue case and within 10 m of the autodissemination and ovitrap stations. At the time of recruitment, AD-PPF devices (Ovitraps filled with 250 mL of water with one sachet of Sumilarv™ 0.5 G Sumitomo Chemical as previously described elsewhere [ 28 ]) were placed in the chosen households in the intervention study site houses. In addition, traps without the PPF mixture were similarly deployed in the control site.…”
Section: Methodsmentioning
confidence: 99%
“…This concept was later adapted to control the mosquitoes that transmit DENV [ 25 ]. This approach has been shown to be effective in reducing mosquito densities in several field trials [ 26 , 27 , 28 ] through the use of pyriproxyfen (PPF), a synthetic analog of a juvenile growth hormone that has high potency at very low concentrations [ 29 ]. Most of these studies showed that AD occurred and successfully reduced the Aedes spp.…”
Section: Introductionmentioning
confidence: 99%